Real-time system for facial emotion detection using GPSO algorithm - Bashir, Mohammed Ghandi; R., Nagarajan, Prof. Dr.; Hazry, Desa, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/